AMALAB-E, A FORMULATED BOTANICAL PRODUCT POTENTIAL AGAINST RICE BLAST INCITANT PYRICULARIA GRISEA - SWAGATIKA ROUT,; S. N. TEWARI, (The Bioscan, 2012)
Formulated organic product was developed by combining a formulating agent (coded A+) with ethanolic extract of Aegle marmelos and screened against Pyricularia grisea, causing blast disease of rice. The bioassay test conducted through standard conidial germination exhibited MIC of A. marmelos extract at 0.1% and mycelial growth at 1%, whereas, the combined formulated Product registered MIC at 0.01% and at 1% respectively in that order. Thus, formulated product improved the efficacy of this botanical product which possesses the potential to be utilized for the management of one of the most destructive diseases of rice blast.